Oribatid mites (Acari, Oribatida) of open and forested habitats of Korčula Island (Croatia) - Seniczak, Stanisław; Kaczmarek, Sławomir; Seniczak, Anna; Rraczyk, Radomir (Biological Letters, 2013)
Oribatid mites were investigated on Korčula Island (Croatia) in various microhabitats in an open habitat (moss on rock, moss on soil) and in stone pine forest floor (moss, litter, rotting wood) in late August 2004. Special attention was paid to the age structure of species. These mites were rather abundant but their species diversity was low. The highest density was observed in patches of moss in the forest floor, and the lowest density was in rotting wood. Among the oribatid mites, only several species were abundant (Achipteria nitens, Zygoribatula propinqua, Pilogalumna crassiclava, Scheloribates initialis, S. laevigatus, and Tectocepheus velatus). Some species were rich in juveniles, while in others the adults dominated.